Anti-membrane Antibodies Persist at Least One Year and Discriminate Between Past Coronavirus Disease 2019 Infection and Vaccination. (27th June 2022) - Amjadi, Maya F; Adyniec, Ryan R; Gupta, Srishti; Bashar, S Janna; Mergaert, Aisha M; Braun, Katarina M; Moreno, Gage K; O'Connor, David H; Friedrich, Thomas C; Safdar, Nasia; McCoy, Sara S; Shelef, Miriam A
Abstract: Background: The consequences of past coronavirus disease 2019 (COVID-19) infection for personal and population health are emerging, but accurately identifying distant infection is a challenge. Anti-spike antibodies rise after both vaccination and infection and anti-nucleocapsid antibodies rapidly decline. Methods: We evaluated anti-membrane antibodies in COVID-19 naive, vaccinated, and convalescent subjects to determine if they persist and accurately detect distant infection. Results: We found that anti-membrane antibodies persist for at least 1 year and are a sensitive and specific marker of past COVID-19 infection. Conclusions: Thus, anti-membrane and anti-spike antibodies together can differentiate between COVID-19 convalescent, vaccinated, and naive states to advance public health and research. Abstract : Antimembrane antibodies persist for at least 1 year and are a sensitive and specific marker of past COVID-19 infection. Also, antimembrane and antispike antibodies together can differentiate between COVID-19 convalescent, vaccinated, and naive states.